Mudanças no sistema tributário e a dinâmica da economia - Pinheiro, Francisco Reginaldo Pinto (1997)
This thesis describes the influence of economics factors such as income concentration levei and the structure of the economy, in the Tax System. lt shows, for instance, how the enlargement of the service sector and the growth of the income concentration can reduce the perforrnance of the Value Added Tax in terrns of the current economic activity. Moreover, in the present discussion about tax reform in Brazil, it must be taken in consideration the influence ofthe economy in the Tax System, mainly its effects in terms of public sector capacity to generate its own revenue to comply with the traditional State functions.